2021
DOI: 10.1136/bcr-2019-233282
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral serous retinal detachment: an unusual complication of HELLP syndrome

Abstract: A 23-year-old primigravida presented to the emergency department with reports of headache. On examination, her blood pressure was found to be 190/140 mm Hg. Her laboratory results were notable for proteinuria, deranged liver function and low platelets. She was diagnosed with HELLP syndrome and was delivered via caesarean section. She noticed diminution of vision 2 days after delivery. Fundus examination revealed bilateral serous retinal detachment involving the maculae. She was managed conservatively and had c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Furthermore, the study also revealed that outcomes for visual acuity were more favorable for patients with preeclampsia than for patients with malignant hypertension, with exacerbating factors including the presence of hypertensive retinopathy and macula location of the SRD [14]. Our patient needed more time to achieve improvement in visual function compared with previous cases [5,6,13].…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Furthermore, the study also revealed that outcomes for visual acuity were more favorable for patients with preeclampsia than for patients with malignant hypertension, with exacerbating factors including the presence of hypertensive retinopathy and macula location of the SRD [14]. Our patient needed more time to achieve improvement in visual function compared with previous cases [5,6,13].…”
Section: Discussionmentioning
confidence: 62%
“…The pathomechanism is proposed to involve generalized endothelial dysfunction and vasospasm in the maternal circulation, resulting in ischemia in retinal pigment epithelium (RPE) and choroid and secondary impairments to the retina [ 10 , 11 , 12 ]. As for visual prognosis, previous case reports have described resolution of SRD within a few weeks to months after treatment of the mother (e.g., emergency cesarean section) [ 5 , 6 , 13 ]. Although few studies have reported factors contributing to the visual prognosis, Lee et al [ 14 ] reported features and factors for visual prognosis in patients with preeclampsia compared with those in patients with malignant hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations